O conteúdo de física no livro didático para a Educação de Jovens e Adultos: uma análise da transposição didática. - Chaba, Priscila Akemi (2019)
The textbook has been considered a relevant object of study in research aimed at pedagogical resources in the school environment, since it is often the main material used by the teacher and potentially can translate the didactic profile in the teaching processes. On the other hand, the textbook represents only transposed cuttings of the knowledge developed throughout the scientific production, which necessarily undergo proper didactic adaptations, in order to get closer to the language of school science. Thus, it is assumed that the knowledge developed in the scientific context goes through the process of didactic transposition aiming at its contextualization in the teaching environment. Thus, the objective of this research was to analyze the elements of didactic transposition present in the physics contents of the textbook directed to High School approved and distributed by PNLD-EJA / 2014 and still in use in educational institutions. The research has a qualitative and analytical approach referring to the characteristics of didactic adaptations of the scientific concepts of physics expressed in the textbook aimed at high school in the modality Education for Youth and Adults, under the theoretical conception of didactic transposition proposed by Yves Chevallard (1991). From the analysis of the elements of didactic transposition, we understand that the material presents a visible concern to link the students' daily life in the approach of the contents, encouraging the formation discourse to work, offering support for the physical knowledge to develop critical citizens in the reflection. and acting in society.